MODEL AND METHOD OF CONTROLLING THE ACTIVE ZONE OF THE VVER-1000 REACTOR DURING CYCLIC TRANSIENT PROCESSES - Зубак, Віктор; Бєлоусов, Валерій; Бєлоусов, Владислав; Кіпріянов, Іван (SWorldJournal, 2023)
The work is devoted to increasing the stability of power distribution in the VVER-1000 nuclear reactor during xenon transients. The calculations modeling the transients were performed. A control method based on optimization of the transient process by ma